OTIMIZAÇÃO DO PROCESSO DE HIDRÓLISE ENZIMÁTICA DE COPRODUTO DA DESOSSA DE FRANGO E APLICAÇÃO DO HIDROLISADO EM HAMBÚRGUER - Bourscheid, Cristiane (2015)
The chicken slaughterhouse generate co-products during slaughter, for example, feathers, bones, blood and guts, usually intended for animal feed with low added value. In bone part of the meat remains bound even after deboning and is a good source of substrate for the enzymatic hydrolysis. The protein hydrolysates may be applied as a nutritional supplement in foods. Given this context, the objective was to optimize the enzymatic hydrolysis process for obtaining protein hydrolyzate coproduct of chicken bones (Gallus gallus domesticus) and the addition of the hydrolyzate as a protein supplement in burger. The co-product selected to carry out the work was thigh and drumstick bone from the chicken bones in a slaughterhouse. The study was conducted in two stages. In the first one a central composite design (CCRD), a total of 17 tests was adopted to evaluate the influence of temperature, enzyme: substrate ratio and time on the degree of hydrolysis. Following the statistical optimization was performed to obtain the best conditions of enzymatic hydrolysis of co-product of chicken bones. The co-product of chicken bones and the optimized protein hydrolyzate were characterized in terms of chemical composition, total amino acids and pattern. In the second step, the hydrolyzate was added as a protein supplement in poultry burger, where two formulations were prepared, Hamburger control (no addition of protein hydrolyzate) and hamburger with hydrolyzed (with addition of 8% protein hydrolyzate). The burgers were characterized in terms of physical-chemical, microbiological and sensory analysis. The optimum conditions for the enzymatic hydrolysis were temperature (T) of 50 ° C, enzyme: substrate ratio (E:S) from 4.96% to time (t) of 110.16 minutes under these conditions the degree of hydrolysis was 24, 0.22 ± 21%. The protein hydrolyzate has the potential to supplementation in food, it is good source of essential amino acids, meeting the recommendations established by FAO / WHO, except for leucine, phenylalanine, and valine, and had a higher concentration of protein fractions from 14.437 kDa and 3,496 kDa. The results obtained for microbiological analysis and physical-chemical analysis of the burger control and burger with hydrolyzed, are in accordance with the respective standards set by law. The burger with hydrolyzate showed 1.02% more protein than the burger control, giving a protein supplementation to the product developed. In the sensorial analysis for flavor attribute evaluators preferred the burger with protein hydrolyzate. The burger with protein hydrolyzate and the burger control achieved 84.2% and 81.8% of general acceptance, respectively. The intention to buy for the burger with added protein hydrolyzate was 76.4% and for the burger control was 67%. In this light, the protein hydrolyzate obtained from chicken bones of the co-product is an alternative to supplementation in foods, as well as add value to the co-product of chicken dessosa and increase the competitiveness of slaughterhouse.